Existence and global asymptotic behavior of S-asymptotically periodic solutions for fractional evolution equation with delay - Li, Qiang; Liu, Lishan; Wu, Xu (Nonlinear Analysis: Modelling and Control, 2023)
This paper discusses the S-asymptotically periodic problem of fractional evolution equation with delay. By introducing a new noncompact measure theory involving infinite interval, we study the existence of S-asymptotically periodic mild solutions under the situation that the relevant semigroup is noncompact and the nonlinear term satisfies more general growth conditions instead of Lipschitz-type conditions. Moreover, by establishing a new Gronwall-type integral inequality corresponding to fractional differential equation with delay, we consider the global asymptotic behavior of S-asymptotically periodic mild solutions, which will make up for the blank of this field.